220 Choice of UK Medical School Predicts Success in The Intercollegiate Membership of The Royal College of Surgeons (MRCS) Examination. (4th May 2021) - Ellis, R; Scrimgeour, D; Cleland, J; Lee, A; Brennan, P
Abstract: Background: UK medical schools vary in terms of factors such as mission, specific curricula and pedagogy. As relatively little is understood about the impact of these differences at a post-graduate level, we examined the relationship between medical school and MRCS success. Method: Using the UKMED database we analysed data on UK medical graduates who attempted MRCS Part A (n = 9729) and MRCS Part B (n = 4644) between 2007-2017. Univariate analysis characterised the relationship between medical school and first attempt MRCS success. Logistic regression modelling identified independent predictors of MRCS success. Results: MRCS pass rates differed significantly between medical schools (P < 0.001). Trainees from standard-entry 5-year programmes were more likely to pass MRCS at first attempt compared to those from extended (Gateway) courses ((Part A (Odds Ratio (OR) 3.72 [95% Confidence Interval (CI) 2.69-5.15]); Part B (OR 1.67 [1.02-2.76])). Non-graduates were more likely to pass Part A (OR 1.40 [1.19-1.64]) and Part B (OR 1.66 [1.24-2.24]). Russell Group graduates were more likely to pass MRCS Part A (OR 1.79 [1.56-2.05]) and Part B (OR 1.24 [1.03-1.49])). Conclusions: Medical programme and medical school are associated with MRCS success. Further research is needed to tease out the relationship between individual factors, medical school and MRCS performance.